Design improvement of toner cartridge using design for assembly method - Hehsan, Haffidzudin; Nordin, Muhammad Alif Haziq (2020)
DFMA or known as Design for Manufacture and Assembly, consists of two main components which are Design for Manufacturing and Design for Assembly. To review the design for product evaluation, DFMA is an important methodolgy to be used. Reducing the number of parts to be assembled in a product is very significant. This can contribute to reducing the cost of assembly and assembly time for manufacturer. DFMA methodology is therefore applied to reduce the cost of the product by selecting a consumer product which is a toner cartridge as a case study of the product. The DFA Worksheet table is used for product evaluation and the original product design is reviewed, improved and re-evaluated. The significant result shows the new toner cartridge design is achievable with fewer parts from 32 to 27 parts. This method is also eligible for application to manufacturing industries to improve the effectiveness of their design.